Can Better Mother-Daughter Relations Reduce the Chance of a Suicide Attempt among Latinas? - Zayas, Luis H. (Hindawi Publishing Corporation, 2011)
National surveys and other research on adolescent Latinas show that adolescent females have higher rates of suicidal ideation, planning, and attempts than other ethnic and racial minority youth. Internalizing behaviors and family conflicts are commonly associated with suicidality in research on adolescents. In the case of Latinas, we explore the connection between adolescent Hispanic cultural involvement, mother-adolescent mutuality, internalizing behaviors, and suicidality. This paper presents data from a study of 232 Latinas, some with a recent history of suicide attempts (n = 122). The results show that higher adolescent Hispanic cultural involvement was associated with greater mother-daughter mutuality and thus led to reduction in the likelihood of suicide attempts. The relationship between mother-daughter mutuality and suicide attempts among Latinas is mediated by specific internalizing behaviors (withdrawn depressive). Our findings highlight the positive effect that Latino cultural values have in the relationship between Latina adolescent and their mothers and confirm the importance that internalizing behaviors and the mother-daughter relationship have for suicide attempters.